Penerapan Model Pembelajaran Problem Based Learning Dipadu Team Games Tournament Melalui Lesson Study Dengan Bantuan Media Pembelajaran Wordwall Untuk Meningkatkan Hasil Belajar IPAS Peserta Didik Kelas IV - Marissa Yudha Kartika; Arin Arianti; Agus Alim (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This study aims to improve science learning outcomes through the Problem-Based Learning learning model combined with the Team Games Tournament with the help of Wordwall learning media. This type of research is Class Action Research. The subjects in this study were students in class IV A at SD Negeri Jetis 01, which consisted of 30 students. While the object of this study is the learning outcomes of the science content. The data used in this study are in the form of qualitative data and quantitative data. Based on the research results, it can be concluded that learning using the Problem-Based Learning model combined with Team Game Tournament with the help of Wordwall learning media can improve student learning outcomes. The learning outcomes in the pre-cycle showed that the level of mastery of learning outcomes was 19 students or 63.33% of the 30 students. In cycle 1 the level of mastery of student learning outcomes increased to 22 students or 73.33% of 30 students. And in cycle II the level of mastery of student learning outcomes increased to 27 students or 90% of 30 students. This research is said to be successful because it has achieved a completeness indicator which is ≥ 80% of the average class with KKM ≥ 73.